Geological structures controlling the placement and geometry of heat sources within the Menengai geothermal field, Kenya as evidenced by gravity study. (May 2019) - Kanda, Isaack; Fujimitsu, Yasuhiro; Nishijima, Jun
Highlights: Updated Bouguer anomaly map reveals a dominant two-fold high density anomalies. The 3-D gravity inversion model helped constrain the density bodies in 3-D space. Strong density gradient highlights host-rock boundary delineated by tectonic faults. Faults and fumaroles indicate coupling of the hydrothermal and magmatic systems. Geomorphology of the dense bodies at depth is interpreted to embay the heat source. Abstract: Menengai volcano is one of the late Quaternary caldera volcanoes formed on a massive shield in the inner-trough of the Kenya rift valley, associated with a high thermal gradient resulting from shallow magmatic intrusion. While drilling of geothermal wells in Menengai area proved the existence of exploitable steam, the complexity of its geological setup has led to various technical setbacks where sited well targets turned out to be unproductive. These challenges were attributed partly to the lack of adequate knowledge to delineate the depth and lateral extent of heat sources. The present work attempts to understand the geological structures that appear control the placement and geometry of heat sources within the Menengai geothermal field. This study utilizes the sensitivity of gravity data to deep structures resolution to determine a three-dimensional (3-D) inversion model. A total of 1823 gravity points were used in generating the Bouguer anomaly, using a Bouguer density of 2.23 g/cm 3 . The model was constrained using estimated densities of drill hole cutting recovered from the geothermal wells. The resultant model was then interpreted together with surface manifestations, geology, and geological structures. Lineament structures were extracted from satellite images and used to enrich the geological structures. The model showed a close relationship between faults and inferred geometry of subsurface volcanic complexes displayed as discrete dike-like bodies in the near-surface environment. The structural system controlling the extent of the dense trachytic body of Olrongai is distinct, but for the caldera, some inference can be made from the results of this study. These faults are interpreted as the feeder dikes of the dense syenitic intrusives, that are hosted within the trachytic formation, and believed to be the heat source for the geothermal system. These structures act as conduits of magma to shallow levels, supplying the much-needed heat to the geothermal reservoir.